PROSES PEMEKARAN DESA PERSIAPAN TAMBAH JAYA KECAMATAN RAMBAH HILIR KABUPATEN ROKAN HULU TAHUN 2014-2015 - Rusmandani "; Raja Muhammad Amin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
The division moratorium village is the first step of the government to make the arrangement number of villages.village expansion proposal has been accepted by BPMPD, but the petition was in the process of considering the central goverment has not issued a decision lifting of moratorium. Therefore, the research wanted to see the expansion process village jaya preparation add Rokan Hulu in 2014-2015. The research objective: fist, to find out how the expansion process village tambah jaya preparation Rambah Hilir subdistrict Rokan Hulu in 2014-2015.second, to find out how a limiting factor not yet achieved the division village tambah jaya proparation in 2014-2015. Data collectected by way of interviews with informants and direct observation. While the analysis of data using qualitative methods to analyze data and use logic argument is based on data obtained in the field by connecting facts, data and information. The survey results that the village expansion preparation Tambah Jaya has become a redistricting process to be completed. In the village chief Rambah, head Rambah Downstream, and BPMPD thera is no problem in completing the requirements division of the village. Then, when seen from the village of inhibing proliferation village that has not been revoked, that village Tambah Jaya preparation add’ve done the preparation of the village expansion in accordance with Law No. 6 of 2014. From the recent indications irregularities in the number of residents and their parties who want interest of blooms unknown village, thus becoming the village redistrcting process preparation Tambah Jaya Rambah Hilir subdistrict Rokan Hulu in 2014-2015.Keywords: Autonomy village, village Expansion